Youthful Choices: A Secondary Analysis of the NFHS-5 Data to Examine Tobacco Use in Indian Adolescent Girls and Young Women - Jobinse Jose; Aditi Chaudhary; Abhishek Ghosh; Sonu Goel (Indian Journal of Psychological Medicine)
Background and aim: Tobacco use among adolescents and young women is a global health concern. This study investigates the prevalence and determinants of tobacco use among adolescents and young women in India. Methods: Based on data from the National Family Health Survey-5, this study explored tobacco use among 241,180 young women aged 15–24 in India. The research investigated determinants of current tobacco use, encompassing any tobacco use in any form, smoked and smokeless tobacco (SLT). Independent variables include demographics, religion, caste, region, education, occupation, body mass index, wealth index, alcohol consumption, and media exposure. We used multivariable logistic regression models to estimate the adjusted odds ratio (OR) and 95% confidence intervals (95%CI). Results: Findings revealed that 1.3% of the population are current tobacco users, with 1.2% using SLT and 0.14% smoking. Significant determinants included age, urban residence, religion, scheduled tribe status, wealth index, education, alcohol co-use, region, and pregnancy/lactation status. Young women (young women, 3.5% > adolescents, 1.5%; OR 1.78, 95%CI 1.65, 1.92), urban dwellers (OR 1.38, 95%CI 1.32, 1.43), and alcohol users (OR 5.6, 95%CI 4.88, 6.33) exhibited higher odds of tobacco use. In contrast, education (higher education OR 0.15, 95%CI 0.13, 0.18) and higher socioeconomic status (richest OR 0.3, 95%CI 0.22, 0.31) were protective factors. Conclusion: Our research offered valuable insights into tobacco use among young Indian women. To effectively curb tobacco use in this population, it is imperative to address the identified determinants and vulnerabilities through tailored public health strategies and policies.